Analysis of the Relationship Between Percentage Coral Cover and Water Quality Effects in Penuktukan, Bali - Trifajriah Lutea Ayu; Munasik; Agus Trianto; Maestro Munru (International Journal of Marine Engineering Innovation and Research, 2024)
The coral reef ecosystem is a diverse ecosystem that provides coastal protection, food sources, and raw materials for medicine, among other ecosystem services. Coral reef research in Penuktukan, Bali, is fundamental given its urgency in preserving the biodiversity and health of existing marine ecosystems. However, the condition of coral reefs in Penuktukan has yet to be widely studied. Hence, information on species diversity, health conditions, and the impact of environmental change and human activities on this ecosystem still needs to be explored. This research is aimed at fill these data gaps by evaluate the health status of coral reefs, identifying species present, and assessing the impacts of environmental and anthropogenic factors on coral reefs in Penuktukan. The study was conducted at eight observation stations to represent differences in environmental characteristics in July 2023. Field observations were conducted to measure water parameters, and underwater Photo Transects were used to determine the percentage of live coral cover. The results obtained on average water parameters include a temperature of 26.4 ° C, a salinity of 32.7‰, a pH meter of 7.7, a brightness of 3 meters, a depth of 3 meters, and 7 meters depth of 7 meters. This study identified coral massive (CM), coral encrusted (CE), and coralfoliose (CF), which were the most prevalent life forms in Penuktukan Village. The average percentage of live coral reefs in Penuktukan Village was 30.42 %, which suggests that coral reefs in Penuktukan Village Waters are in a medium condition, which is suitable for supporting coral reef ecosystem resilience and development.